2006
DOI: 10.1123/rsj.30.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Student Recreation Centers: A Comparison of Users and Non-Users on Psychosocial Variables

Abstract: Undergraduate ( n = 561) and graduate ( n = 104) students at a large mid-Atlantic university were surveyed to determine their usage patterns and beliefs about the climate of a newly constructed student recreation center (SRC) on their campus. Analyses attempted to identify differences between those students who used the facility ( n = 547) and those who did not ( n = 118) in relation to gender, age, year on campus, stage of change for exercise, and motivational orientation. Results revealed that SRC users were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 12 publications
5
42
0
Order By: Relevance
“…Most students reported living either on-campus or off-campus within one mile of the university. The data from this research is fairly consistent with results from prior studies (Watson et al, [2006]; Zizzi et al, [2004]; Miller et al,[2008]). We can suggest that users are more likely to be male, Caucasian, non-smokers, live on-campus or off-campus within a mile of the college or university, age 21 and under, not involved in any type of extracurricular activity, and have no health concerns.…”
Section: Summary Conclusion and Future Directionssupporting
confidence: 82%
See 1 more Smart Citation
“…Most students reported living either on-campus or off-campus within one mile of the university. The data from this research is fairly consistent with results from prior studies (Watson et al, [2006]; Zizzi et al, [2004]; Miller et al,[2008]). We can suggest that users are more likely to be male, Caucasian, non-smokers, live on-campus or off-campus within a mile of the college or university, age 21 and under, not involved in any type of extracurricular activity, and have no health concerns.…”
Section: Summary Conclusion and Future Directionssupporting
confidence: 82%
“…In response to the rise in obesity rates, society is looking toward fitness and recreation centers as a contributing factor in trying to combat this nationwide problem, which is affecting millions of young adults (Watson, Ayers, Zizzi, & Naoi, 2006). The construction of student fitness and recreation centers on college campuses has become a massive business over the last several years (Miller, Noland, Rayens, & Staten, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Lindsey and Sessoms (2006) found that female students were more likely to participate in campus recreational sports, while juniors and seniors consider these campus recreational programs as an important indicator of college selection. In contrast, some past research (Barcelona & Ross, 2002;Terzioğlu & Yazıcı, 2003;Young et al, 2003;Zizzi et al, 2004;Balcı & İlhan, 2006;Tekin et al, 2007;Miller et al, 2008;Lindsey et al, 2009;Lindsey, 2012;de Jager & Gbadamosi, 2013) found that male students were more likely to be participants and other earlier studies (Watson II et al, 2006;Miller et al, 2008;Milton & Patton, 2011) showed that lower-division students (freshmen and sophomores) were more likely to participate in campus recreational facilities. However, earlier research (Shank & Beasley, 1998;Frauman, 2005;Clemes et al, 2008;Sökmen, 2011;Moosmayer & Siems, 2012) indicated that there were no differences in the perceived importance of quality of campus life facilities with respect to students' gender.…”
Section: Review Of Related Literaturementioning
confidence: 88%
“…Marital status was also a contributing indicator, while results of a number of studies (Terzioğlu & Yazıcı, 2003;Frauman, 2005;Miller et al, 2008) revealed that married students were less likely to participate in campus recreational programs. Several studies mentioned that off-campus (Barcelona & Ross, 2002;Frauman, 2005) or on-campus students (Watson II et al, 2006;Miller et al, 2008;Milton & Patton, 2011) and part-time employed students (Frauman, 2005) were more likely to participate in campus recreational sports programs. Nevertheless, some earlier studies (Aldemir & Gülcan, 2003;Thomas & Galambos, 2004) found that demographic factors did not have an effect on students' satisfaction with campus facilities.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation